Procedures of building plan approvals at Majlis Daerah Kuala Selangor / Norsuhadah Sukardi - Sukardi, Norsuhadah (Universiti Teknologi Mara, Perak, 2014)
Practical training is the last medium 6 semester diploma of building surveying. Therefore, I’m Norsuhadah binti Sukardi daughter has started practical training at 25. November.2013 until 29. March.2014 in Majlis Daerah Kuala Selangor. I was stationed at the Building Control Department to undergo practical training for four and a half months of this. Majlis Daerah Kuala Selangor before I got this, I was interviewed by the secretary of the host Majlis Daerah Kuala Selangor Tuan Haji Azhari Bin Sairin. Later, I received practical training in this Majlis Daerah Kuala Selangor. I’m thankful to Allah SWT for my permission to practical training perfect. After I placed the building control department, I will try my best to conduct these duties as a student here with good practical and excellent.